Data Quality Control and Data Analysis of Body-Scanner Measurement Values in Children and Adolescents - Vogel, M.; Fischer, A.L.; Bucher, C.; Kiess, W.; Kirsten, Toralf (2014-Leipziger-Research-Festival, 2014)
Introduction LIFE child as a part of the 'Leipzig Research Centre for Civilization Diseases' is a longitudinal cohort study aiming, inter alia, at monitoring normal development in children and adolescents from fetal life to adulthood. As an important part of the study, anthropometric dimensions are measured via classic methods, e.g. stadiometer or tape measure (ca. 15 items), but also via 3D body scanner technology (ca. 150 items). Because of missing standards data quality control and analysis of the latter one is a particular challenge. Methods We address the problem of absent reference values by using the data itself as a reference sample. Applying the LMS-method using the VGAM/GAMLSS packages [XXX] on a reference sample which is large enough results in age and gender corrected standard deviation scores (SDS) respectively percentile curves. A combination of variable clustering and clustering of values using these SDS is applied to the detect groups of dependend variables and peculiar cases respectively. Results In LIFE child the current reference sample consists of around 4000 scans of 1700 children. The age dependend l, m, and s values for each item are generated by dedicated R-routines and stored in a relational database system. The transformation algorithm by Cole is implemented as database function and dynamically applied on all associated raw data. Conspiciuous values can be detected using the SDS itself or the SDS in comparison with the belonging variable cluster and/or taking into account the follow-up data of the respective participant. These values can be reported and visualized using automated routines.